High Electron Mobility in [1]Benzothieno[3,2-B][1]Benzothiophene Field-Effect Transistors: Toward N-Type BTBTs - Usta, Hakan; Kim, Dojeon; Ozdemir, Resul; Zorlu, Yunus; Kim, Sanghyo; Ruiz Delgado, M. Carmen; Kim, Myung-Gil (Amer Chemical Soc, 2019)
The first example of an n-type [1]benzothieno[3,2-b][1]benzothiophene (BTBT)-based semiconductor, D-(PhFCO)-BTBT, has been realized via a two-step transition metal-free process without using chromatographic purification. Physicochemical and optoelectronic characterizations of the new semiconductor were performed in detail, and the crystal structure was accessed. The new molecule exhibits a large optical band gap (similar to 2.9 eV) and highly stabilized (Delta E-LUMO = 1.54 eV)/pi-delocalized lowest unoccupied molecular orbital (LUMO) mainly comprising the BTBT pi-core and in-plane carbonyl units. The effect of out-of-plane twisted (64 degrees) pentafluorophenyl groups on LUMO stabilization is found to be minimal. Polycrystalline D(PhFCO)-BTBT thin films prepared by physical vapor deposition exhibited large grains (similar to 2-5 mu m sizes) and "layer-by-layer" stacked edge-on oriented molecules with an in-plane herringbone packing (intermolecular distances similar to 3.25-3.46 angstrom) to favor two-dimensional (2D) source-to-drain (S -> D) charge transport. The corresponding TC/BG-OFET devices demonstrated high electron mobilities of up to similar to 0.6 cm(2)/V.s and I-on/I-off ratios over 10(7)-10(8). These results demonstrate that the large band gap BTBT pi-core is a promising candidate for high-mobility n-type organic semiconductors and, combination of very large intrinsic charge transport capabilities and optical transparency, may open a new perspective for next-generation unconventional (opto)electronics.
Ruiz Delgado, M. Carmen/0000-0001-8180-7153; Ha, Young-Geun/0000-0001-9632-3557; Ozdemir, Resul/0000-0002-7957-110X; Facchetti, Antonio/0000-0002-8175-7958; Usta, Hakan/0000-0002-0618-1979; Harbuzaru Harbuzaru, Alexandra/0000-0003-2434-3182; Demirel, Gokhan/0000-0002-9778-917X;